Assessing Mosque-Based Zakat Fitrah Collection: Legal and Sharia Perspectives from Rural Indonesia - Elvia, Siti; Amri Syahputra Sir, Ali; Latifah Zahira, Hana; Cahyati, Cyce; Jazila, Aliya; Riani, Julita; Sophia Intan, Angel (El-kahfi | Journal of Islamic Economics, 2025)
This study investigates the implementation of zakat fitrah collection at Masjid Baiturrahim, Pulau Batu Hamlet, Jujuhan Ilir Subdistrict, through the lens of Islamic law. The research aims to evaluate whether the procedures carried out by mosque administrators align with Islamic legal principles, especially concerning the appointment of zakat administrators (amil), distribution methods, and compliance with the eight rightful recipients (asnaf). Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation involving mosque management and local residents. The findings reveal that while the collection and distribution of zakat fitrah are driven by strong religious values and community participation, several elements deviate from Islamic jurisprudence. Notably, there is no formal appointment of amil, distribution does not fully consider all eight asnaf as mentioned in Qur’an Surah At-Taubah: 60, and the measurement of zakat (rice) lacks uniformity. These findings align with previous studies that highlight similar challenges in rural zakat practices, where traditional management often overshadows formal institutional structures. The discussion draws upon relevant Qur’anic verses, Hadiths, and scholarly opinions from classical and contemporary Islamic economists and jurists to assess the implications of the findings. It is recommended that mosque-based zakat management be integrated with recognized zakat institutions and follow standardized guidelines to enhance accountability and social impact. Strengthening legal literacy among community leaders and residents is also essential to ensure that the religious objectives of zakat—purification, justice, and welfare—are fully realized. This study contributes to ongoing efforts to improve grassroots zakat management in accordance with Sharia principles